Analisis Nilai Sosial Dalam Novel Aral Karya Fatih Zam - Alhakim, Helmi Taufiq; Supriadi, Oding; Mujtaba, Sahlan (Peneliti.net, 2024)
Literary work is the result of human creativity which is the embodiment of the imagination or creativity of the writer based on the reality of his life in society. Literature is known to have mimetic properties which in Greek means imitation. Imitation in this case is a picture of the reality of life or reality that is centered on the universe. Thus, what is contained in literature is actually the reality that exists in life, but it is added with the ideas and ideas of the author which makes it a work of fiction. Literary works have various functions, one of which is an educational function. It is said to have an educational function because basically literature contains many positive values ​​that readers can take and apply in everyday life. One form of literary work is a novel. This research aims to describe. (1) describe the social values ​​in the novel Aral by Fatih Zam. This study uses Burhan Nurgiyantoro's theory of intrinsic elements and Jubaedi's social values. Intrinsic elements are elements that (directly) participate in building the story. It is this element that makes the novel tangible and is often encountered by readers when reading novels. Social values ​​are a set of individual attitudes that are used as a standard of behavior and valued as a truth to get a harmonious and democratic society. Thus, social values ​​have a very important position for society, nation and state. Social values ​​function as a reference for behavior in interacting with others so that empowerment can be accepted in society. The subject in this study is the novel Aral by Fatih Zam .The data collection technique in this research is document study. The results of this study also found social values ​​which include: (1) the value of mutual help, (2) the value of caring, (3) the value of loyalty, (4) the value of kinship, and (5) the value of responsibility.